Pengaruh Pendidikan Kesehatan dengan Games Kit terhadap Peningkatan Pengetahuan dan Sikap tentang Kesehatan Reproduksi dan Seksualitas (Studi Kasus di SMA Negeri 14 Semarang) - Umi Masviroh; Muhammad Azinar (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Mental health is a vital aspect of overall well-being, involving physical, psychological, social, and Adolescents are vulnerable to risky sexual behaviors that may lead to unwanted pregnancies and sexually transmitted infections. Health education in schools is essential to prevent such problems. This study aimed to analyze the effect of using educational Games Kit media on improving students’ knowledge and attitudes regarding reproductive health and sexuality. A pre-experimental one-group pretest–posttest design was applied involving 98 eleventh-grade students at SMA Negeri 14 Semarang, selected through purposive sampling. The intervention consisted of two sessions: Games Kit Wordwall for reproductive health education and Games Kit Cards & Puzzle for sexuality education. Data were collected using validated questionnaires and analyzed with the Marginal Homogeneity test (α = 0.05). The results showed a significant improvement (p = 0.000) in both knowledge and attitudes after the intervention. Before the program, many students had only moderate knowledge and neutral attitudes, while after the intervention, most demonstrated good knowledge and positive attitudes. Games Kit as a playful and interactive medium successfully increased student engagement, facilitated the understanding of sensitive topics, and encouraged active participation. These findings suggest that educational games can be an effective strategy for enhancing reproductive health and sexuality education among adolescents.